Tradition in Creative Writing - May, Adrian. author. aut Link
XII, 183 p. 1 illus.
Keywords: Tradition in Creative Writing: Finding Inspiration Through Your Roots encourages writers to rediscover sources of creativity in the everyday, showing students how to see your writing as connected to your life. Adrian May addresses a key question for many beginning writers: Where do you get your ideas from? May argues that tradition does not mean anti-progress—but is instead a kind of hidden wealth that stems from literary and historical traditions, folk and songs, self and nature, and community. By drawing on these personal and traditional wellsprings of inspiration, writers will learn to see their writing as part of a greater continuum of influences and view their work as having innate value as part of that cultural and artistic ecology. Each chapter includes accessible discussion, literary and critical readings, creative examples, and writing exercises. While the creative examples are drawn from song lyrics and poetry, the writing exercises are appropriate for all genres. Undergraduates and practitioners will benefit from this guide to finding originality in writing through exploring sources of creative inspiration.